Sustainbility indicators measuring the immeasurable - Bell, Simon 1957- (Earthscan Pub., 1999)
[This book] addresses the crucial issue of sustainability: how can it be measured. In contrast to the current trends in developing sustainability indicators, the authors discuss the advantages of taking a holistic and more qualitative approach